Surgical site infections after liver retransplantation: Incidence and risk factors. Issue 8 (24th June 2014) - Shah, Harshal; Hellinger, Walter C.; Heckman, Michael G.; Diehl, Nancy; Shalev, Jefree A.; Willingham, Darrin L.; Taner, C. Burcin; Perry, Dana K.; Nguyen, Justin
<x xml:space="preserve">Abstract</x> Surgical site infections (SSIs) after liver transplantation (LT) are associated with an increased risk of graft loss and death. The incidence of SSIs after LT and their risk factors have been determined for first LT but not for second LT. The importance of reporting the incidence of SSIs risk‐stratified by first LT versus second LT is not known. All patients undergoing second LT at a single institution between 2003 and 2011 (n = 152) were reviewed. The Kaplan‐Meier method was used to estimate the cumulative SSI incidence. Relative risks (RRs) and 95% confidence intervals (CIs) from Cox proportional hazards regression models were used to evaluate associations of potential risk factors with SSIs after second LT. Thirty‐one patients developed SSIs (6 superficial SSIs, 1 deep SSI, and 24 organ/space SSIs). The cumulative incidence of SSIs 30 days after LT was 20.8% (95% CI = 14%‐27%), which was slightly but not significantly higher than the previously reported incidence of SSIs after first LT at our institution between 2003 and 2008 (16%, RR = 1.32, 95% CI = 0.90‐1.93, P = .16). Units of transfused red blood cells [RR (doubling) = 1.38, 95% CI = 1.02‐1.86, P = .04] and hepaticojejunostomy (RR = 2.22, 95% CI = 1.05‐4.72, P = .04) were the only factors associated with SSIs after second LT in single‐variable analysis. The associations weakened in a multivariate analysis (P = .07 and P = .07, respectively), potentially because of the correlation of red blood cell transfusions and hepaticojejunostomy (P = .08). In conclusion, the incidence of SSIs after second LT was slightly higher but not significantly different than the published incidence of SSIs (16%) after first LT at the same institution. Significant independent risk factors for SSIs after second LT were not identified. Risk stratification for retransplantation may not be necessary when the incidence of SSIs after LT is being reported. Liver Transpl 20:930–936, 2014. © 2014 AASLD.